Cooperative Multi-Agent Learning in a Complex World: Challenges and Solutions - Du, Yali (Proceedings of the AAAI Conference on Artificial Intelligence, 2024)
Over the past few years, artificial intelligence (AI) has achieved great success in a variety of applications, such as image classification and recommendation systems. This success has often been achieved by training machine learning models on static datasets, where inputs and desired outputs are provided.However, we are now seeing a shift in this paradigm. Instead of learning from static datasets, machine learning models are increasingly being trained through feedback from their interactions with the world. This is particularly important when machine learning models are deployed in the real world, as their decisions can often have an impact on other agents, turning the decision-making process into a multi-agent problem.As a result, multi-agent learning in complex environments is a critical area of research for the next generation of AI, particularly in the context of cooperative tasks. Cooperative multi-agent learning is an essential problem for practitioners to consider as it has the potential to enable a wide range of multi-agent tasks.In this presentation, we will review the background and challenges of cooperative multi-agent learning, and survey our research that aims to address these challenges.